Comparison and influence of metal dopants on the opto-electrical, microstructure and gas sensing properties of nanostructured indium oxide films. (February 2022) - Ghasemi, Fatemeh; Ghasemi, Mohsen; Eftekhari, Leila; Soleimanian, Vishtasb
Graphical abstract: Highlights: Effects of metal dopants on the optical, microstructure and gas sensing properties of In2 O3 films is investigated. Among metal dopants, including Sn, Zn, Mn and Ag, silver metal shows better sensing results. The correlation between the physical characteristics and gas sensing properties is studied. 3% doping of Ag is an effective method to improve the electro-optical and gas sensing properties of In2 O3 films. The effects of crystallite size, dislocation density, lattice strain and roughness on sensitivity is determined. Abstract: Thin films of pure and Sn, Zn, Mn, and Ag-doped indium oxide (In2 O3 ) with a thickness of 150 nm are grown by co-deposition using thermal evaporation technique and annealed at 500 °C. The crystal lattice strain, dislocation density, optical band gap, surface roughness, and gas sensitivity of the films are studied. Comparison of AFM results shows that the Ag-doped In2 O3 has the highest roughness. The ethanol vapor sensing results demonstrate that 3% Ag-doped In2 O3 films have higher sensitivity at the operating temperature of 325 °C to 1000 ppm of ethanol vapor, due to the presence of more roughness and defects than other films. The response and recovery times of this sample at 1000 ppm ethanol vapor were 32 and 51 s, respectively. Finally, it is shown how 3% of metal impurities in the In2 O3 layer can affect the optical, microstructural, and gas sensing parameters of the samples, and also investigated the correlation between them.